Menumbuhkan Cinta Lingkungan, Literasi dan Wirausaha Melalui Program “Bermekaran” di Desa Karang Bunga Kabupaten Barito Kuala - Noor, Muhammad Aidin; Damaiyanti, Varinia Pura; Risnawati, Risnawati; Julvionisar, Julvionisar; Aulia, Hilyatun; Fadila, Helya; Salina, Salina; Situmorang, Luciandro Gideon (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2024)
The capability of the Karang Bunga Village community to the potential and problems of the village is the problem behind community empowerment through the BERMEKARAN (Babarasih, Meng teach, and Merangkul) program which is designed to break down environmental problems, lack of interest in literacy and local culture, deadlock in the development of micro, small and medium enterprises (MSMEs), and strengthening village documents through social mapping. The activities implemented are based on the theory of community empowerment, namely enabling (efforts to develop community capabilities through the 'teaching' program), then empowering (improving community soft skills through the 'embracing' program), and protecting (through mapping potentials and problems to support community knowledge about the social and economic conditions of the village). The program achievements, namely strengthening community awareness of the environment, increasing literacy culture to local cultural knowledge, assisting the management of micro, small and medium enterprises (MSMEs), and mapping the potential and problems of the village through social mapping to support the village's interests in managing and handling the potential and problems that exist in the village. The program is identified to create a stronger, more independent and empowered community. Communities that care about the environment, are knowledgeable, and have sustainable economic businesses to make the community an agent of change in the stability of life to bring constant growth and development. With a clean environment, stable economy, and educated community, the welfare level of the community can increase, creating a better environment for future generations.